A Comparative Study of Language Learning Strategies among English Department Students at IAIN Kediri - Burhanuddin, Muhammad (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2025)
Utilizing appropriate language learning strategy may influence student’s learning process. In fact, many students do not employ the right learning strategy. This study aims to investigate students’ learning strategy used by students of English Department of IAIN Kediri. The design used in this research is a quantitative descriptive design with comparative study method and the research involved 120 students, from 4th and 6th semester of English Department IAIN Kediri. The data were collected using the Strategy Inventory for Language Learning (SILL) questionnaire, Version 7.0 by Rebecca L. Oxford, which includes 50 items. The findings reveal that both 4th and 6th semester students most commonly used metacognitive strategies, while compensation strategies were the least used. Overall, 4th semester students were high users of learning strategies (M = 3.53), while 6th semester students were moderate users (M = 3.48). Further analysis by major showed variations: in tourism and translation majors, metacognitive strategies were most used and compensation strategies least used. In literature majors, metacognitive strategies remained the most used, but the least used strategies differed—memory strategies for 4th semester students and social strategies for 6th semester students. These results indicate significant differences in strategy use across majors, leading to the conclusion that the null hypothesis is rejected, and the alternative hypothesis is accepted—there are differences in language learning strategies among tourism, translation, and literature students at IAIN Kediri.